Business Mentoring Program for Indonesian and Malaysian SMEs - Nuvriasari, Audita; Harsoyo, Titik Desi; Hudin, Norlaile Salleh; Ab Wahab, Nur Yuhainis (PT Inovasi Pratama Internasional, 2025)
SMEs play a strategic role in supporting economic growth in developing countries. The purpose of this community service activity is to provide assistance to Batik SMEs in Indonesia and Malaysia to develop their businesses. Community service activity partners are batik SMEs from Yogyakarta, Indonesia and Malaysia. The program implementation method includes observation, interviews, counseling and assistance. Activities are carried out offline by carrying out activities at the SME's place of business and online in the form of webinars. The extension materials include: business management, entrepreneurial marketing, digital marketing, green marketing and environmental sustainability. The results of this activity are expected to provide a positive contribution in increasing the knowledge and skills of partners in business management so that they can maintain the sustainability of their business in the long term.